Heterogeneity of the barrier properties of the colon in rat - Bekusova, Viktoria; Fatyykhov, Ilyas; Amasheh, Salah; Markov, Alexander (Biological Communications, 2021)
The incidence of colorectal cancer in different parts of the large intestine is not the same, as tumors more often appear in the distal part of the colon compared to the proximal one. The purpose of this study was to investigate heterogeneity of the barrier properties of the colon and clarify the effects of Prostaglandin E2 and interleukin-1beta on its different parts. An in-depth analysis of short circuit current, transepithelial electrical resistance and paracellular permeability for sodium fluorescein in Ussing chambers showed that the proximal part of the colon was less permeable compared to the distal one and the substances had different effects on the parameters of permeability in different parts of the colon. We suppose that heterogeneity of the barrier properties of the colon and various effects of their regulation by local molecular agents may determine different incidence of pathologies in the colon.